Transcriptome and metabolome for identifying key metabolites impacting the Vibrio parahaemolyticus in Litopenaeus vannamei - Jin, Jiaojiao; Chen, Nanxiong; Hu, Yicheng; Chen, Yibin; Yin, Bin; Wang, Xu; Shen, Yuchun; Li, Sedong (Frontiers in Marine Science, 2024)
Introduction Shrimp is an important aquaculture species worldwide. Vibrio parahaemolyticus (VP) is an opportunistic pathogen of Litopenaeus vannamei that can cause diseases such as acute hepatopancreatic necrotic disease (AHPND), resulting in significant losses to the shrimp farming industry. Methods In this study, We analyzed two shrimp populations by transcriptomics and non-targeted metabolomics, which exhibited significant differences in resistance to VP. Through integrated analysis, we identified genes and metabolites linked to the development of shrimp's resistance to VP. Results and discussion The analysis revealed that the differential metabolism of flavonoid compounds, especially quercetin, significantly influences the expression of shrimp's resistance to VP. Supplementing feed with an appropriate quantity of quercetin has the potential to increase the expression of crucial genes in the NF-κB pathway, including TLR and AP1, along with the expression of the antibacterial peptide crustin, resulting in a decreased mortality rate. Together, these results indicate that an appropriate amount of quercetin can strengthen the immune response of shrimp to VP, thereby reducing the incidence of AHPND.